A new species of Porta Distant, 1903 (Hemiptera: Heteroptera: Rhyparochromidae: Ozophorini) - Kondorosy, Előd; Varga, Katinka; Zsalakovics, László (Zootaxa, 2012)
Porta longirostris sp. nov. (Hemiptera: Heteroptera: Rhyparochromidae: Rhyparochrominae: Ozophorini) from Borneo is described and figured. A supplement is given to the key to the species of the genus.